Ethnoecological study on the utilization of plants in Ciletuh-Palabuhanratu Geopark, Sukabumi, West Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Wulandari I, Iskandar BS, Parikesit, Hudoso T, Iskandar J, Shanida SS, Megantara EN, Gunawan EF. 2021. Ethnoecological study on the utilization of plants in Ciletuh-Palabuhanratu Geopark, Sukabumi, West Java, Indonesia. Biodiversitas 22: 661-674.  Plants can provide benefits for community as food, medicine, fuel, building materials, furniture, and others. Plant utilization should be conducted sustainably in a region with high importance of geological, biological, and cultural diversity, such as in Ciletuh-Palabuhanratu Geopark, Sukabumi, West Java, Indonesia. This study aimed to reveal: (i) plant utilization by local community in Ciletuh-Palabuhanratu Geopark based on land cover; and (ii) community dependence on the plants being utilized. Method used in this study was mixed of qualitative and quantitative methods using direct observation, semi-structured and structured interviews data collection techniques. The result of study showed that the community in Ciletuh-Palabuhanratu Geopark still uses plants for food (80 species), medicinal plants (73 species), livestock fodder (9 species), firewood (27 species), building materials, furniture (38 species), and others (23 species). The highest plant utilization came from gardens (131 species), home gardens (99 species), natural forests (77 species), dry-paddy fields, and wet-paddy fields (7 species). Generally, various agroecosystems and also forest in Ciletuh-Palabuhanratu Geopark have an important role in providing plant products to fulfill the daily needs of rural people.
Keywords: Ciemas Village community, Pelabuhanratu Geopark, plant utilization